Chemical Profiling Ethyl Acetate Extract of Basilicum polystachyon Leaves and Exploration of Anticancer SIRT1 Inhibitors Using In Silico Approach - Tukiran, Tukiran; Raihan, Muhammad (Indonesian Journal of Chemistry, 2025)
Cancer significantly increases prevalence and mortality rate making it a serious health concern currently, including breast cancer. The development of new drugs is a major effort to solve the cancer problems. Natural products are the primary source of medicinal compounds believed to have lower toxicity and side effects than synthetic drugs. This research aimed to reveal the chemical profile of the ethyl acetate extract of Basilicum polystachyon leaves. Through an in silico approach, this research studied the anticancer mechanism against the sirtuin1 (SIRT1) at the molecular level. Molecular docking simulations were performed to understand the interaction behavior of potential compounds as SIRT1 inhibitors. Based on these results, 117 individual compounds were successfully identified in the ethyl acetate extract. Molecular docking simulation revealed that ten compounds could inhibit SIRT1 better than the control inhibitor, indicating that these compounds have potential as anticancer agents. The prediction of these compounds' physicochemical properties and pharmacokinetics showed promising results and fulfilled the medicinal compound's criteria. These findings can be the basis for the application of phytochemical compounds as anticancer drugs, specifically potential compounds in B. polystachyon leaves.